THE INFLUENCE OF BOARD INTERLOCKING ON FIRM PERFORMANCE WITH FOREIGN OWNERSHIP AS A MODERATING VARIABLE (Evidence from LQ 45 Companies for The Period 2015-2018) - Ayu Isnaeni; Agung Juliarto (Diponegoro Journal of Accounting, 2021)
This study aims to examine the influence of board interlocking on firm performance, with foreign ownership as moderating variable. The dependent variable of the study is firm performance (Return On Asset), whereas board interlocking as the independent variable moderated by the foreign ownership variable. The control variables of the study are ownership concentration, institutional ownership, board size, board independence, firm size, firm age and financial leverage. This research used the companies sample that listed in LQ-45 in Indonesia Stock Exchange on 2015-2018 period. This study is a quantitative study using secondary data in the form of annual reports 20 companies for 4 years (80 observations). The sampling method used in the study is purposive sampling. The hypotheses testing used moderated regression analysis with the help of SPSS version 24 software. These results are accordance with Resource Based Theory and Resource Dependence Theory which indicate that board interlocking has a positive effect on firm performance.; However, foreign ownership does not moderate the effect of board interlocking on firm performance.